DEPENDENCE OF TENSIONS ARISING IN THE STEM OF THE KNITTING NEEDLE WHEN THE NEEDLE HITS THE WEDGE ON THE INFLEXIBILITY OF THE NEEDLE-WEDGE PAIR - PLESHKO, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The efficiency of knitting machines, in particular their productivity and fabric quality, largely depends on the durability of the needles, which, in turn, depends on the dynamic loads that arise in the zone of impact interaction of the needles with the wedges of knitting systems. Previous studies have shown that when a knitting needle hits a wedge, shock waves of stress appear in its shaft, which is one of the main causes of needle failure (destruction of the needle hook, etc.). In this case, when solving the problem of determining the magnitude of the stresses arising in the needle rod, the case of a hard impact of the needle (rod) on the wedge is considered. In reality, when the needle hits the wedge, an elastic impact occurs, due to the rigidity of the needle-wedge pair. Studies show that an effective way to reduce the dynamic loads acting on the needle during knitting machine operation is to reduce the inflexibility of the needle-wedge pair. However, the issue of the influence of the inflexibility of the needle-wedge pair on the dynamics of tensions arising in the needle stem has not been practically studied, which creates certain problems in the design of knitting machines. The object of research is the knitting machine needle and the process of its interaction with the wedges of knitting systems. When solving the problems set in this work, modern methods of theoretical research were used, based on the theory of shock wave propagation in flat stem elements during longitudinal impact. The research objective is to investigate the influence of the inflexibility of the needle-wedge pair of a knitting machine on the tensions that arise when the needle hits the wedge, and to develop a method for the influence of the inflexibility of the needle-wedge pair on the impact tensions in the needle stem during its interaction with the wedge during the knitting process. Analysis of the obtained dependencies allows us to conclude that the inflexibility of the needle-wedge pair affects the magnitude of the tensions in the needle stem caused by the shock wave. At the same time, a decrease in inflexibility contributes to a decrease in the magnitude of the tensions in the needle stem. As is known, the needle has a complex geometric shape. Therefore, when the needle hits the wedge, a complex stress field arises in its body, which depends on the geometric shape of the needle. The obtained equations are only some approximation of the description of the process of changing the tensions in the needle body when it hits the wedge.